KAJIAN PRINSIP KEADILAN HUKUM DALAM ASAS LEGALITAS HUKUM PIDANA ISLAM - Mahfudz, Yudia (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
The principle of legality is one of the principles that has the most basic position, making it a main principle in criminal law. The principle of legality in criminal law has limitations in advocating values related to legal justice. The aim of this research is to find out how the benefits of the principles of legality of Islamic criminal law are used as a basis for updating the content of current law. The method used in this research is Normative Law which discusses the principles related to legal justice contained in the principles of legality of Islamic criminal law which will be researched comprehensively and exploratoryly. The results of this research state that the principle of legality of Islamic criminal law has a strong relationship with religious principles because it comes from a clear source, namely the Al-Qur'an. So, this principle has power related to spirituality and flexibility. Islamic criminal law has flexibility in its implementation because it has classifications regarding the efficiency of non-criminal acts.